Marconi : the man who networked the world - Raboy, Marc, 1948- (Oxford University Press, 2016)
Marc Raboy gives us the first real account of Marconi's vital role as the wizard of wireless, industry developer, and consummate political insider. Raboy's impeccably researched biography will help guide histories of global media in the years ahead.